Peningkatan perekonomian masyarakat melalui pelatihan pengolahan Se’i di Desa Ponain Kabupaten Kupang, Nusa Tenggara Timur - Sulmiyati, Sulmiyati; Malelak, Gemini E. M.; Jelantik, I Gusti Ngurah; Lalus, Matheos Filipus; Benu, Imanuel; Telupere, Frangky M.S.; Lawa, Alvrado Bire (Universitas Muhammadiyah Mataram, 2026)
AbstrakPelaksanaan kegiatan PKM pada kelompok Tani Nefo Tua Desa Ponain Kecamatan Amarasi Kabupaten Kupang bertujuan untuk meningkatan peningkatan kesejahtraan anggota kelompok melalui penyelsaian masalah belum maksimalnya pengelolaan daging dalam pembuatan se’i, kemasan daging se’i dan pemasaran produk hasil yang lebih luas. Solusi yang ditawarkan adalah penggunaan alat pengasapan yang dirancang khusus dalam pengolahan se’i, penggunaan teknologi alat vakum untuk pengemasan serta starategi membangunan jaringan penjualan melalui pemanfaatan toko modern. Metode yang digunakan melalui penyuluhan partisipatif, praktek pelatihan secara langsung. Hasil kegiatan ini telah memberikan dampak positif bagi kelompok tani terkait pengetahuan tentang dinamika kelompok, analisis pemasaran serta penggunaan alat pengasapan yang benar dan efektif dalam menghasilkan produk se’i yang memiliki kualitas gizi dan layak. Berdasarkan hasil evaluasi, tingkat penerimaan Kelompok Tani Nefo Tua terhadap produk se’i menunjukkan respons yang baik, yang ditunjukkan 50% anggota menyukai produk dan menilai cita rasa produk memiliki karakteristik khas se’i. Aspek peningkatan kapasitas, terjadi peningkatan pengetahuan 66,67% setelah pelatihan, yang didukung dengan penilaian 66,67% keterampilan tim pelaksana. Aspek pengembangan usaha 83,33% menilai se’i memiliki prospek ekonomi, dan 66,67% menyatakan minat untuk mengembangkannya, meskipun daya tari kemasan berada pada kategori sedang dengan 50% menilai menarik. Kesimpulan pelatihan pembuatan se’i daging sapi menghasilkan produk yang layak dipasarkan dan berpotensi menjadi usaha prospektif bagi kelompok tani melalui penerapan standarisasi produk, ketersediaan bahan baku, dan manajemen pemasaran yang mendukung peningkatan kesejahteraan. Kata kunci: ekonomi; kelompok tani nefo tua; kupang; se’i. Abstract The first problem faced by the Nefo Tua Farmers Group community engagement partners is Ponain Village, Amarasi District, Kupang Regency. The development of se'i as a processed meat business product has yet to be developed optimally. The second problem is that the marketing of se'i products needs to be maximised by improving packaging. The third problem is marketing analysis and development prospects for se'i. The solution offered consists of two programs, namely the first program, carrying out se'i processing using smoking equipment and the second program, marketing se'i products using labelled vacuum packaging. The third program is marketing analysis and product development of se’i. The methods provided include participatory counselling, practical training, and direct demonstrations in processing beef se'i and packaging the resulting se'i products, as well as guidance and mentoring. As a result of the service activities, the Nefo Tua Farmers group gained knowledge about group dynamics and business and marketing analysis, as well as applying and demonstrating knowledge about processing beef into se'i using a closed smoker and practically packaging the products produced. Based on the evaluation, the acceptance of the se’i product by the Nefo Tua Farmer Group was categorized as favourable, with 50% of participants reporting a preference for the product and perceiving its sensory attributes as representative of the distinctive characteristics of se’i. In terms of capacity building, a 66.67% increase in knowledge was observed following the training, supported by a 66.67% positive assessment of the facilitation team’s technical competence. From a business development perspective, 83.33% of identified se’i as having economic potential, and 66.67% expressed an intention to pursue their development as an entrepreneurial activity, although the perceived attractiveness of the packaging remained moderate, with 50% of rating it as appealing. In conclusion, the training on beef se’i production yielded a marketable product and demonstrated its potential as a viable opportunity for farmer groups through the implementation of product standardization, ensured raw material availability, and effective marketing management to support improved livelihoods Keywords: economy; nefo tua farmer groups; kupang; se’i